Disney characters as moral role models: a discourse analysis of Coco and Encanto - Vaidya, Ruta; Osman, Yousra (Frontiers in Communication, 2024)
Popular culture characters and narratives can influence people’s understanding of moral actions, and thus guide their behaviors accordingly. Films have proven to be strong anchors in people’s understanding of morality. We examine the perception of resilience as a moral characteristic in examining not just how people become resilient (thereby focusing on impact and action) but also to study ‘resilience’ as a discourse and discussion in society as a moral message. We argue that popular culture narratives, particularly Disney films, help reinforce moral meanings of resilience. By conducting a discourse analysis of two films- Encanto and Coco and particularly focusing on resilience, we aim to contribute to a deepened understanding of Disney’s role in producing morality through diverse narratives and characters who serve as role models.